2002
DOI: 10.1007/s11743-002-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Micellar association in simultaneous presence of organic salts/additives

Abstract: Viscosity measurements under Newtonian flow conditions had been performed on cetyltrimethylammonium bromide (CTAB) aqueous solutions in the combined presence of sodium salts of aromatic acids (sodium salicylate, NaSal; sodium benzoate, NaBen; sodium anthranilate, NaAn) and organic additives (1-hexanol, C 6 OH; n-hexylamine, C 6 NH 2 ) at 30°C. On addition of C 6 OH or C 6 NH 2 , the viscosity of 25 mM CTAB solution remained nearly constant without salt as well as with a lower salt concentration. This is due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Added salt may affect the partitioning of alcohol between the micelle and aqueous phase. 29 It is thus of great interest to see how an additive at different micellar solubilisation sites can inuence the association morphology and its subsequent physical properties. It would then be easier to mimic more complex biological systems since they involve hydrophobic interactions like simple surfactant morphologies (micelles or vesicles).…”
Section: Introductionmentioning
confidence: 99%
“…Added salt may affect the partitioning of alcohol between the micelle and aqueous phase. 29 It is thus of great interest to see how an additive at different micellar solubilisation sites can inuence the association morphology and its subsequent physical properties. It would then be easier to mimic more complex biological systems since they involve hydrophobic interactions like simple surfactant morphologies (micelles or vesicles).…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Many investigations have been carried out in the literature on the formation of viscoelastic wormlike micelles in a variety of surfactant systems with the addition of the above type of organic salts. [9][10][11][12][13][14][15][16][17][18] The organic salt screens the electrostatic repulsion between the charged head groups, and induces one dimensional micellar growth by decreasing the effective cross-sectional area per head group of the surfactant molecule. [19] Anionic surfactants are widely produced and consumed in vast quantities than any other surfactants because of their high detergency and low cost of manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…The rod-like micelles are formed at 0.1 mol L -1 KBr and the worm-like micelles are formed at above 0.2 mol L -1 KBr. Kumar et al [13] and Desai et al [14] studied the micellar growth in presence of alcohol and amines and they found that octanol is more effective in promoting the sphere-to-rod transitions in surfactant systems; the penetration of the surfactant rich film by octanol helps to overcome the head group repulsion of the surfactant molecules [15,16].…”
Section: Introductionmentioning
confidence: 99%